Missing the bandwagon: Nonnative species impacts still concern managers - Sara E. Kuebbing; Daniel Simberloff (NeoBiota, 2015)
Recent critics of invasion biology advocate reduced efforts against nonnative species, arguing that attempts to manage invasions are often costly and futile and that managers are indiscriminately managing species regardless of their impact. Whether this criticism has affected ground-level operations is unknown. A survey of land stewards of a major conservation NGO reveals that this plea has not been heeded; in fact, managers report that they would increase nonnative species management if more resources were available. While respondents overwhelmingly listed nonnative, invasive species as their highest priority for management, we found little evidence supporting the criticism that practitioners focus on nonnative species with minimal ecological impact. Additionally, we found that more conservation practitioners reported managing problematic “weedy” native species over nonnative species that are not invasive. Our results indicate that these managers are selective rather than profligate, targeting species that are having a demonstrable impact or are likely to do so. They feel hamstrung by resource shortages despite their rigorous target selection. Why the increasing literature calling for changed treatment of nonnatives has not led to changed operations is uncertain. Possible reasons are that the critics are not prescriptive or unified about management prioritization, or that these managers simply reject the proposed new paradigm.